Live and non-live tracking of a moving target using an MPEG video file - Mahi Hassou; Nadia Mohammed; Shahd Hassou (College of Education for Pure Sciences, 2012)
Abstract The process of diagnosis and classification of moving targets occupies a major place in applications that use a computer. Facts in our world is a visual moving objects deal with video scenes that contain an unspecified number of moving targets. Here, the idea was to cut and diagnosis and follow-up to these goals through sequential video images. The idea of this paper is to take a video file (MPEG) and convert it to a set of images (JPG format) for the purpose of setting the goal of any moving object tracking, i.e. a moving target within a video file if it's a person, a car or a ball, etc. For Recognition the facility of subtracting between the frames is used. where Tracking is executed using Rectangle algorithm. Programs have been written in "Visual C#" as it considered one of the most efficient visual languages.